Targeting tumor-associated macrophages with STING agonism improves the antitumor efficacy of osimertinib in a mouse model of EGFR-mutant lung cancer - Lin, Ziying; Wang, Qiwei; Jiang, Tao; Wang, Weihua; Zhao, Jean J. (Frontiers in Immunology, 2023)
Despite the impressive clinical response rate of osimertinib, a third-generation EGFR-TKI, as a frontline treatment for patients with EGFR-mutant non-small-cell lung cancer (NSCLC) or as a salvage therapy for patients with T790M mutation, resistance to osimertinib is common in the clinic. The mechanisms underlying osimertinib resistance are heterogenous. While genetic mutations within EGFR or other cancer driver pathways mediated mechanisms are well-documented, the role of tumor cell and tumor immune microenvironment in mediating the response to osimertinib remains elusive. Here, using a syngeneic mouse model of EGFR-mutant lung cancer, we show that tumor regression elicited by osimertinib requires activation of CD8+ T cells. However, tumor-associated macrophages (TAMs) accumulated in advanced tumors inhibit CD8+ T cell activation and diminish the response to osimertinib. These results are corroborated by analyses of clinical data. Notably, reprogramming TAMs with a systemic STING agonist MSA-2 reinvigorates antitumor immunity and leads to durable tumor regression in mice when combined with osimertinib. Our results reveal a new mechanism of EGFR-TKI resistance and suggest a new therapeutic strategy for the treatment of EGFR-mutant tumors.